2022
DOI: 10.1002/adem.202200749
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Soft Magnetoactive Devices with Thiol‐Click Photopolymer Composites

Abstract: Magnetoresponsive polymers have gained increased attention in the design of soft actuators as they can be spatially as well as temporally activated and enable an external noninvasive control of movement. By introducing the magnetoresponsive properties in photocurable resins, one can fabricate personalized and complex structures (via vat photopolymerization 3D printing), whose movement can be conveniently controlled by an external magnetic field. Advancing from acrylate-based photopolymers, which often suffer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In another study we showed that this stabilizer is also able to catalyze transesterification reactions due to its Brønsted acidity. 35 Herein, we exploited this feature to print magneto-active composites with additional functions such as thermo-activated mendability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In another study we showed that this stabilizer is also able to catalyze transesterification reactions due to its Brønsted acidity. 35 Herein, we exploited this feature to print magneto-active composites with additional functions such as thermo-activated mendability.…”
Section: Resultsmentioning
confidence: 99%
“…41 On the other hand, coordinative bonds might be formed between the Fe 3 O 4 nanoparticles and the unreacted thiol groups, which anchor the ller to the photopolymer matrix. 35 In the presence of the organic phosphate, the photopolymer composites are able to undergo thermo-activated dynamic bond exchange reactions across the functional -OH and ester groups (transesterication). The change in the viscoelastic properties was studied by rheometer experiments.…”
Section: D Printing and Materials Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The novel APdA monomers were then subject to photopolymerization with a stoichiometric ratio with the commonly used trithiol (1,1,1-tris-(hydroxymethyl)-propanetris-(3-mercaptopropionate) (TMPMP). Similar systems have been widely studied with organic alkynes 25,26 , acrylates 27,28 and vinyl esters 29 for the preparation of photopolymers for a range of biomaterials applications. The monomer conversion (MC) was analysed by RT-FTIR spectroscopy, in which the reaction was followed by a decrease in the alkyne band at 2130 cm -1 (Figure 2b, full spectrum SI-16).…”
mentioning
confidence: 99%